Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/nph.17639
|View full text |Cite
|
Sign up to set email alerts
|

Structural diversity and tree density drives variation in the biodiversity–ecosystem function relationship of woodlands and savannas

Abstract: Positive biodiversity-ecosystem function relationships (BEFRs) have been widely documented, but it is unclear if BEFRs should be expected in disturbance-driven systems. Disturbance may limit competition and niche differentiation, which are frequently posited to underlie BEFRs. We provide the first exploration of the relationship between tree species diversity and biomass, one measure of ecosystem function, across southern African woodlands and savannas, an ecological system rife with disturbance from fire, her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 96 publications
(123 reference statements)
5
16
0
Order By: Relevance
“…Which ones of taxonomic diversity (species richness), structural diversity and functional metrics of Hmax are the main drivers of AGB? In line with previous studies (Luo et al, 2019;Aponte et al, 2020;Godlee et al, 2021), we predicted that CWMHmax and structural diversity attributes would have stronger effects on AGB than species richness and functional diversity (range and divergence) of Hmax.…”
Section: Applied Vegetation Sciencesupporting
confidence: 89%
See 1 more Smart Citation
“…Which ones of taxonomic diversity (species richness), structural diversity and functional metrics of Hmax are the main drivers of AGB? In line with previous studies (Luo et al, 2019;Aponte et al, 2020;Godlee et al, 2021), we predicted that CWMHmax and structural diversity attributes would have stronger effects on AGB than species richness and functional diversity (range and divergence) of Hmax.…”
Section: Applied Vegetation Sciencesupporting
confidence: 89%
“…We asked the following research questions: Which ones of taxonomic diversity (species richness), structural diversity and functional metrics of Hmax are the main drivers of AGB? In line with previous studies (Luo et al, 2019; Aponte et al, 2020; Godlee et al, 2021), we predicted that CWMHmax and structural diversity attributes would have stronger effects on AGB than species richness and functional diversity (range and divergence) of Hmax. How do structural diversity attributes and functional metrics of Hmax mediate the effects of species richness and environmental factors on AGB? Because we expected that structural diversity would better reflect local environmental influence than functional trait‐based metrics, we hypothesized that structural diversity would mediate the effects of species richness and environmental conditions on AGB better than functional metrics of Hmax. …”
Section: Introductionsupporting
confidence: 87%
“…Overall, the SEM results suggested that at small spatial scales (0.01 and 0.04 ha), the number of trees should be more important than mycorrhizal dominance in driving both tree diversity and AGB (Figure 3) and, hence, driving the positive DBR (Chisholm et al, 2013). This is partly because each individual positively contributes to total AGB, and abundance may promote diversity via a statistical or sampling effect at the scales where a tree community is far from being saturated by species (Appendix S1: Figure S9a; Fung et al, 2020; Godlee et al, 2021). Actually, many previously described mechanisms (e.g., complementarity and selection effect) that can drive positive BEF relationships mainly work at small spatial scales (Luo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…We used IBM SPSS AMOS 24.0 to build the integrative model, a graphic-based software to visualize correlations and regression weights among variables [ 32 ]. The structural equation modeling method applied in the software has been widely used in recent ecological modeling studies [ 4 , 8 ]. We built the environment suitability, tree growth, and management models and evaluated their relationships with the productivity model.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have characterized the relationships of plant productivity with species richness [ 4 ] and climate [ 5 ], the effects of crown attributes and stand structure on tree productivity [ 6 ], and the effects of management policies on plant productivity [ 7 ]. Most of these studies have used integrative modeling approaches to explore the relationships among variables [ 4 , 8 ], but few have evaluated correlations using multi-sourced factors (e.g., environment, plant attributes, and management) at the individual level. In addition, the difficulty of interpreting the significance of the outputs of these modeling analyses often impedes the ability to extract practical insights that could be applied to improve productivity.…”
Section: Introductionmentioning
confidence: 99%